1997
DOI: 10.1029/97jd01078
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the troposphere over the Indian Ocean during the monsoonal transition

Abstract: Abstract. The atmosphere over the equatorial Indian Ocean is a unique environment in which to study the chemical and radiative effects of an intense source of anthropogenic emissions from the northern hemisphere directly coupled to the relatively pristine background conditions present in the southern hemisphere. As an initial investigation into the role of the intertropical convergence zone (ITCZ) on interhemispheric transport of pollutants, a number of trace atmospheric species were measured aboard the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 42 publications
9
88
1
Order By: Relevance
“…21. These strong gradients, including the sharp gradient across the ITCZ, were first noted in measurements made on the pre-INDOEX and INDOEX ship cruises (e.g., Rhoads et al, 1997;Moorthy et al, 1997;Jayaraman et al, 1998Jayaraman et al, , 1999Jayaraman et al, , 2001Satheesh et al, 1998;Naja et al, 1999;Stehr et al, 2002;Quinn et al, 2002;Chand et al, 2001Chand et al, , 2003Kamra et al, 2003;Norman et al, 2003;Nair et al, 2004;Naja et al, 2004), as well as in aircraft observations during INDOEX (e.g., Ramanathan et al, 2001;Reiner et al, 2001;Gabriel et al, 2002a;Pelon et al, 2002;de Reus et al, 2002), and shortly thereafter were corroborated to be a general feature of the broader region based on numerous pieces of evidence, including further in situ observations, satellite retrievals and model simulations (e.g., Rajeev et al, 2000Rajeev et al, , 2004Rajeev and Ramanathan, 2001;Collins et al, 2001Collins et al, , 2002de Laat et al, 2001a, b;Lelieveld et al, 2001;Lawrence et al, 2003a;Minvielle et al, 2004a, b;Moorthy et al, 2005a;Satheesh et al, 2006a, b;Vinoj et al, 2007;Verma et al, 2008). In addition to this generally strong gradient of pollutants in the SAW-ABC, these observations and modeling studies have also shown a very abrupt transition between the polluted NH air masses and more pristine SH air in the MBL at the ITCZ, which can be considered a "chemical ITCZ" …”
Section: Transit Times Lofting In the Itcz And Interhemispheric Exchmentioning
confidence: 99%
“…21. These strong gradients, including the sharp gradient across the ITCZ, were first noted in measurements made on the pre-INDOEX and INDOEX ship cruises (e.g., Rhoads et al, 1997;Moorthy et al, 1997;Jayaraman et al, 1998Jayaraman et al, , 1999Jayaraman et al, , 2001Satheesh et al, 1998;Naja et al, 1999;Stehr et al, 2002;Quinn et al, 2002;Chand et al, 2001Chand et al, , 2003Kamra et al, 2003;Norman et al, 2003;Nair et al, 2004;Naja et al, 2004), as well as in aircraft observations during INDOEX (e.g., Ramanathan et al, 2001;Reiner et al, 2001;Gabriel et al, 2002a;Pelon et al, 2002;de Reus et al, 2002), and shortly thereafter were corroborated to be a general feature of the broader region based on numerous pieces of evidence, including further in situ observations, satellite retrievals and model simulations (e.g., Rajeev et al, 2000Rajeev et al, , 2004Rajeev and Ramanathan, 2001;Collins et al, 2001Collins et al, , 2002de Laat et al, 2001a, b;Lelieveld et al, 2001;Lawrence et al, 2003a;Minvielle et al, 2004a, b;Moorthy et al, 2005a;Satheesh et al, 2006a, b;Vinoj et al, 2007;Verma et al, 2008). In addition to this generally strong gradient of pollutants in the SAW-ABC, these observations and modeling studies have also shown a very abrupt transition between the polluted NH air masses and more pristine SH air in the MBL at the ITCZ, which can be considered a "chemical ITCZ" …”
Section: Transit Times Lofting In the Itcz And Interhemispheric Exchmentioning
confidence: 99%
“…Surface measurements of several trace gases, aerosols and meteorological parameters were made along with the soundings. For a detailed description and results of this campaign see Rhoads et al (1997) one year later in 1999. The Indian R/V Sagar Kanya sailed from southern India to the Indian Ocean east of Madagascar (Fig.…”
Section: Observationsmentioning
confidence: 99%
“…Generally, a typical O 3 profile over the Indian Ocean can be divided into several layers. In the marine boundary layer O 3 mixing ratios are low (outside of coastal regions), caused by an O 3 -destructive environment (Rhoads et al, 1997;Lal et al, 1998;de Laat and Lelieveld, 2000;Lawrence and Lal, 2001). Between the boundary layer and 8 km O 3 mixing ratios are higher.…”
Section: Introductionmentioning
confidence: 99%
“…The diurnal variation of ozone observed over the oceanic environment is different from that observed over land as discussed in the earlier studies (Johnson et al, 1990;Rhoads et al, 1997;Bhugwant et al, 2001). Over the land, ozone shows an increase few hours after sunrise reaching peak values before noon and starts decreasing in the afternoon reaching low values at night (Lal et al, 2000;David and Nair, 2011).…”
Section: Diurnal Variation In Ozonementioning
confidence: 57%